Role of Human Recombinant Erythropoietin (rHuEPO) in Perinatal Asphyxia-a randomized controlled trial - Mehnaz, Syeda; Chowdhury, MAK Azad; Yasmeen, BH Nazma; Rahman, Md Masudur; Akter, Rowshan Jahan; Afrin, Manifa; Begum, Mahmuda (Northern International Medical College Journal, 2018)
Background : Perinatal asphyxia is an insult to the fetus or newborn infant due to lack of oxygen (hypoxia) and/or a lack of perfusion (ischemia) to various organs, which will manifest as difficulty in establishing spontaneous respiration evident by delayed cry after birth, at least after one minute. World-wide, perinatal asphyxia accounts for about 900,000 deaths each year. In Bangladesh it is a major cause of neonatal death. A substantial proportion of the children that survive suffer late effects such as cerebral palsy and epilepsy. Objective : To determine the efficacy of erythropoietin in improving the neurological outcome of term neonates with perinatal asphyxia (HIE stage II and III). Materials and methods : A Randomized Controll Trial was carried out in the Neonatal ward and NICU of Dhaka Shishu Hospital from 1st April 2014 to 30th Sep 2015. A total 68 neonates with perinatal asphyxia (both HIE stage II and III) who fulfill the inclusion criteria were enrolled and randomly assigned to intervention group (n=35) and control group (n=33). Intervention group received rHuEPO 300- 500 U/kg/dose daily subcutaneously for 5 days within first 48 hours of birth along with the standard treatment protocol and control group received standard treatment protocol only. Results : Baseline clinical characteristics, USG of brain during hospital stay were almost similar in both groups. Statistically significant effect was noted in seizure control, tolerance of oral feeding, hospital stay and neurological outcome at 3 months of age (p=008). USG of brain at 3 months of age also improved significantly (p=0.027). Conclusion : This study demonstrates the effectiveness of early administration of rHuEPO to term neonates with moderate to severe asphyxia, beneficial effect on short term outcomes like seizure control, tolerance of oral feeding and neurological outcome at 3 months of age. A large multicenter study would be done for further evaluation of these findings. Northern International Medical College Journal Vol.10(1) Jul 2018: 330-334